Streaming music, streaming capital - Drott, Eric 1972- (Duke University Press, 2024)
"In Streaming Music, Streaming Capital, Eric Drott examines the relationships between music, technology, economy, and culture within the ecosystem of online streaming. Attentive to the way the rise of online platforms has reordered how music is circulated and consumed, Drott offers a Marxist interrogation of capitalism and its relation to music consumption. Drawing on digital sources and economic ephemera as evidence, Drott puts forth an overview of streaming's role within the music industry as a commentary on platform economy and economic power. By interrogating the tensions between streaming's benefits and pitfalls, Drott's work highlights important socioeconomic issues in music's digital ascendency, from accessibility, distribution, and data collection, to musical value, labor, and artist treatment"--